Critical Necessity of Local Monitoring and Enforcement for Sustainable Governance of Forests - Pandey, Deep Narayan (Indian Forester, 2010)
A large number of variables may potentially determine the success or failure of sustainable governance of forests, yet the success in finding the necessary condition has remained elusive. Recently, the Nobel Prize for 2009 in Economic Sciences has been awarded to Elinor Ostrom who made major contributions to our understanding of the governance of forests and common pool resources. Ostrom has spent considerable amount of time and efforts with the International Forestry Resources and Institutions programme that produced some of the most useful research relevant to practitioners of natural resource management. This paper reviews the recent research that clearly demonstrates that even when a number of other factors are taken into account, higher levels of local monitoring and enforcement of locally-made rules can result in improved regeneration and lower the possibility of forest degradation across a variety of ecological, economic and social contexts. This understanding has immediate practical utility for joint forest management in India.